Implementasi Strategi PAIKEM Dalam Pembelajaran Bahasa Arab Di SDS Sunan Kalijogo Jabung - Fajar Ledianto; Ahmad Nuruddin; Nurul Hayati; Khoirul Mustaqim; Faishol Mahmoed Adam Ibrahim (Discovery, 2025)
Arabic language learning in elementary schools in Indonesia has an important role in creating a generation that understands Islam and Arabic culture. Although considered difficult and boring, PAIKEM (Active, Innovative, Creative, Effective, and Fun Learning) strategies provide an effective solution by making learning more interesting through word games, songs, and others that can increase student motivation. This study used a qualitative research method with a Narrative research design. Data were obtained through interviews, observations, and documentation, then analyzed thematically. The interviews were conducted with 2 Arabic teachers and 10 students. This study found that the implementation of PAIKEM successfully increased academic knowledge as well as developed students' critical thinking, communication, and cooperation skills. The implementation of PAIKEM was also effective in increasing students' learning motivation and creating a more interactive and interesting classroom environment. The results of the analysis show that despite some challenges, PAIKEM has great potential to be implemented more widely and sustainably with further improvement and development. This research provides strong evidence that PAIKEM can be an effective model for improving the quality of Arabic language learning at SDS Sunan Kalijogo Jabung.